Ovonic Switches Enable Energy-Efficient Dendrite-like Computing - Kang, Unhyeon; Lee, Jaesang; Oh, Seungmin; Song, Hanchan; Park, Jongkil; Kim, Jaewook; Park, Seongsik; Jang, Hyun Jae; Kim, Sangbum; Yi, Su-in; Kumar, Suhas; Lee, Suyoun (American Chemical Society, 2026)
Over the past decade, dendrites of neurons, which were previously thought to perform only information pooling and networking, have now been shown to express complex temporal dynamics, Boolean-like logic, arithmetic, signal discrimination, and edge detection. Mimicking this rich functionality could offer a powerful primitive for neuromorphic computing. Here, using Ovonic threshold switching in Sb–Te-doped GeSe, we demonstrate a single two-terminal component capable of self-sustained dynamics and universal Boolean logic in addition to XOR operations (which is traditionally thought to require a network of active components). We then employed logic-driven dynamics to detect and estimate the gradients of edges in images. The Ovonic switch exhibits properties of a half adder and a full adder in addition to discriminative logic accommodating inhibitory and excitatory signals. We show that this simple computational primitive offers a highly improved energy efficiency. As such, this work paves the path for potentially emulating dendrites for efficient postdigital neuromorphic computing.